Let there be light : the real story of her creation - Finck, Liana (Random House, 2022)
"In this ambitious and transcendent graphic novel, Liana Finck turns her keen eye to none other than the Old Testament, reimagining the story of Genesis with a God as a woman, Abraham as a resident of New York City, and Rebekah as a robot, among many other delightful twists. In Finck's retelling, the millennia-old stories of Adam and Eve, Abraham and Isaac, and Jacob and Esau haunt the pages like familiar but partially forgotten nursery rhymes--transmuted by time but still deeply resonant. With her trademark insightfulness, wry humor, and supple, moving visual style, Finck accentuates the latent sweetness and timeless wisdom of the original text, infusing it with wit and whimsy while retaining every ounce of its spiritual heft. Let There Be Light is a testament to the fact that old stories can live forever, whether as ancient scripture or as a series of profound and enchanting cartoons. The Book of Genesis is about some of the most fundamental questions that we can ask, pertinent across the millennia: What does it mean to be human? What is the purpose of our lives? How do we treat one another? The stories that attempt to answer these questions are an immediate link with the people who first told them. Unable to fathom the holiness and preciousness of that notion, or put it into words, Finck set out to depict it. The result is a true story of creation, rendered by one of our most innovative creators"--